The Jute Genome - Zhang, Liwu.; Khan, Haseena; Kole, Chittaranjan (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is the first comprehensive compilation of deliberations on jute botanical descriptions, germplasm resources, genetic diversity and population structure, DUS test and DNA fingerprinting, interspecific hybridization, classical genetics, cytology and cytogenetics, genetic transformation; and detailed enumeration on molecular mapping, genome sequencing initiatives of three major jute fiber producing countries, interspecific and intergeneric comparative genomics, organellar genomes, elucidation on functional genomics and genomics resources and database. Genetics and genomics of bast fiber development, biotic stress resistance, abiotic stress tolerance, and flowering pathways have also been discussed. It also presents a narrative on the power of molecular markers and genomics technology on jute breeding. Altogether, the book contains about 400 pages over 21 chapters authored by internationally reputed experts on the relevant field in this crop. This book will be useful to the students, teachers and scientists in the academia and relevant private companies interested in agronomy, genetics, pathology, entomology, physiology, molecular genetics and breeding, genetic engineering, and structural and functional genomics.
Chapter 1. Economic Importance of Jute -- Chapter 2. Botany of Jute (Corchorus spp.) -- Chapter 3. Chemistry of Jute and Its Applications -- Chapter 4. Germplasm Resources in Jute -- Chapter 5. DUS Test and DNA Fingerprinting Construction of Jute Varieties -- Chapter 6. Jute Interspecific Hybrids: Development, Characterization and Utilization -- Chapter 7. Classical Genetics, Cytogenetics and Traditional Breeding in Jute -- Chapter 8. Challenges of Jute Transformation -- Chapter 9. Molecular Linkage Mapping: Map Construction and Mapping of Genes/Qtls -- Chapter 10. Jute Genome Sequencing: An Indian Initiative -- Chapter 11. Jute Genome Sequencing: A Bangladeshi Initiative -- Chapter 12. Jute Genome Sequencing: A Chinese Initiative -- Chapter 13. Comparative Genomics and Synteny within Cochorus Species and Among Malvaceaes Genomes -- Chapter 14. Organelle Genome Sequencing and Phylogenetic Relationship of Jute -- Chapter 15. Functional Genomics of Jute -- Chapter 16. Jute Genomic Resources and Data Base -- Chapter 17. Genetics and Genomics of Bast Fiber Development -- Chapter 18. Genetics and Genomics of Biotic Stress Resistance of Jute -- Chapter 19. Genomics and Genetics of Drought and Salt Tolerance in Jute -- Chapter 20. Flowering Pathway of Jute Based on Genomic Data -- Chapter 21. Power of Molecular Markers and Genomics Technology on Jute Breeding.
Keywords: Botany; Genetics; Biotechnology; Agriculture; Plant Science; Genetics and Genomics; Biotechnology; Agriculture